Gestión de las pequeñas empresas de los distritos Tarapoto, Morales, la Banda de Shilcayo y su influencia en el nivel de competitividad empresarial en el año 2009 - Miranda Saavedra, Abraham (2011)
The development of this thesis focuses on the study of small business as a generator and revitalizing the economy in the economic hub comprising the districts of Morales - Tarapoto - Shilcayo The band recorded in the register of micro and small enterprises in the region St. Martin added a total of 118 analyzed fiscal year 2009, for they developed a survey based on the major components of business management, and analysis addresses the management of small businesses and the influence of the same in return , there are several papers in international, national and local levels that address the issue because MSEs generate employment and boost the economy , but in the case of this thesis is addressed exclusively to small business to an analysis of management elements that can have the same contrast to micro-enterprises mostly subsistence. The legal basis of the work is supported by the current regulations related to micro and small enterprises such as: "Legislative Decree No. 1086, Act to promote competitiveness, formalization, development of micro and small enterprises and access to decent employment promulgated June 28, 2008, Law No. 29, 152 established the implementation and operation of the fund research and development for the competitiveness FIDECOM of micro and small business February 15, 2009 The theoretical bases used are among others the theory of capacities dynamic human capital as the basis for the development of any company in the same examines the dynamic environment, adaptability to change, the role of organizational learning and knowledge society is discussed in general business management with key points such as the analysis of Strengths, Weaknesses , Opportunities and Threats (SWOT), defining the mission, vision, competitive advantages, comparisons and more. Concluding that the management of small businesses in the district of Tarapoto Morales and La Banda de Shilcayo positively influence business competitiveness in 2009 , overall management of small businesses in the district of Tarapoto and La Banda de Morales Shilcayo was positive financial indicators such as liquidity, leverage and profit margin, except in the internal organizational analysis which shows marked deficiencies in strategic planning with a lack of management tools.